Bridging Realities: Navigating Pop-Culture Media for Equitable Muslim Portrayals through the Prism of Moderation in Post-9/11 - Fauzan, Muhammad Nuril (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
The influence of media on the formation of attitudes towards Muslims and Arabs in the period following the 9/11 attacks resulted in the propagation of harmful stereotypes and the increase in hate crimes targeting Muslims and Arabs during this time. This was also spread by the role of media, including popular culture media, in disseminating these negative narratives. Using a qualitative approach, this study aims to examine the media’s endeavours to depict Muslims in a positive portrayal and the dearth of meaningful sources documenting these empathetic endeavours through the prism of moderation, especially in post-9/11. This article argues that Evelyn Alsultany's notion of Simplified Complex Representation serves as a gateway for the media's effort to showcase Muslims and Arabs in a more nuanced way.. There are tons of instances that have been analysed from TV dramas, movies, and comics to demonstrate how the media shapes people’s perspectives of Muslims and Arabs. The article contends that media is not merely a mirror of societal views but a powerful agent capable of shaping and modifying perceptions.